2015
DOI: 10.1177/0284185115603246
|View full text |Cite
|
Sign up to set email alerts
|

Combination of radiofrequency ablation with transarterial chemoembolization for treatment of hepatocellular carcinoma: experience from a Danish tertiary liver center

Abstract: Combination therapy with RFA and TACE for unresectable HCC, compared to TACE alone, may offer a survival benefit for a selected group of patients with HCC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Therefore, we are now conducting a study in which the role of CLIPS and JIS scoring systems is elucidated in stratifying the patients with HCC who are strictly at BCLC stage B in our patient population. Finally, the etiology of HCC, and its treatment strategies as well, is different in different countries (2), and therefore, our results may not be generalized or directly applicable to patients in other parts of the world.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Therefore, we are now conducting a study in which the role of CLIPS and JIS scoring systems is elucidated in stratifying the patients with HCC who are strictly at BCLC stage B in our patient population. Finally, the etiology of HCC, and its treatment strategies as well, is different in different countries (2), and therefore, our results may not be generalized or directly applicable to patients in other parts of the world.…”
Section: Discussionmentioning
confidence: 89%
“…Hepatocellular carcinoma (HCC) mainly involves patients already affected with chronic hepatitis or liver cirrhosis due to hepatitis B or C viral infection (1) or alcohol (2). Therefore, the prognostic assessment and choice of therapeutic modalities, such as liver resection, local ablation therapy, transcatheter arterial chemoembolization (TACE), and liver transplantation strongly depends not only on the grade of cancer spread (tumor staging), but also on the grade of residual liver function (liver disease stage) (3).…”
Section: Introductionmentioning
confidence: 99%
“…The appropriate timing for TACE combined with RFA for HCC is controversial [29][30][31]. Bharadwaz et al [32] suggested Figure 3. A 37-year-old man with HCC recurrence 5 months after liver transplantation.…”
Section: Discussionmentioning
confidence: 99%
“…The prognosis was closely associated with tumor relapse, tumor number, albumin (ALB), prothrombin time (PT) and platelet (PLT) count (8). Another study in a Danish tertiary liver center compared 18 cases of TACE & RFA combined treatment with 18 cases of TACE treatment alone and found that combined TACE & RFA treatment provided superior therapeutic effects (9). A meta-analysis of 21 studies with 3,073 cases showed that TACE & RFA combined treatment could significantly increase both the short-term and long-term survival rates and improve the prognosis (10).…”
Section: Introductionmentioning
confidence: 99%